Laparoscopic cholecystectomy in situs inversus totalis: A review article - Sunder Goyal (Archives of Clinical and Experimental Surgery, 2016)
Background: Situs inversus totalis is a rare congenital anomaly characterized by transposition of organs to the opposite side of the body. Diagnosis and treatment of cholelithiasis in such cases pose a challenge to the operating surgeon because of an atypical clinical picture and the contra lateral disposition of the viscera. Methods: A literature search using the PubMed and Cochrane databases identified articles focusing on the key issues of laparoscopy cholecystectomy in situs inversus. Conclusions: Without doubt, laparoscopic cholecystectomy in these patients is technically more demanding but still feasible and should be performed by trained and experienced laparoscopic surgeons. Difficulty is encountered in skeletonizing the structures in Calot's triangle, which usually requires extra time than in patients with a normally located gall bladder. [Arch Clin Exp Surg 2016; 5(3.000): 169-176]